Rethinking intra-party cohesion: Towards a conceptual and analytical framework. (September 2019) - Close, Caroline; Gherghina, Sergiu
Intra-party cohesion (IPC) is a concept extensively used to assess institutional change and behaviour in legislative and party politics. In spite of its popularity, there is confusion about its meaning mostly derived from its multidimensional nature. This article aims to clarify the understanding of this term across three different fields of research (legislative studies, party factionalism and Hirschman's theory applied to intra-party dynamics) and to build a conceptual framework that integrates several analytical dimensions. It uses quantitative network-based analysis of bibliographic data to provide a descriptive account of connections between these fields of the literature. Based on this, it identifies major challenges in the study of IPC and reveals the necessity to investigate it beyond ideology and legislative arena. To this end, we argue and illustrate how Hirschman's theory applied to three levels of analysis allows us to formulate a framework suitable for the study of IPC.